Mutation of chromatin regulators and focal hotspot alterations characterize human papillomavirus–positive oropharyngeal squamous cell carcinoma. Issue 14 (1st April 2019) - Haft, Sunny; Ren, Shuling; Xu, Guorong; Mark, Adam; Fisch, Kathleen; Guo, Theresa W.; Khan, Zubair; Pang, John; Ando, Mizuo; Liu, Chao; Sakai, Akihiro; Fukusumi, Takahito; et al.
Abstract : Background: Human papillomavirus (HPV)–associated oropharyngeal cancer is a disease clinically and biologically distinct from smoking‐related head and neck squamous cell carcinoma (HNSCC). Despite its rapidly increasing incidence, the mutational landscape of HPV+ oropharyngeal squamous cell carcinoma (OPSCC) remains understudied. Methods: This article presents the first mutational analysis of the 46 HPV+ OPSCC tumors within the newly expanded cohort of 530 HNSCC tumors from The Cancer Genome Atlas. A separate exome sequencing analysis was also performed for 46 HPV+ OPSCCs matched to their normal lymphocyte controls from the Johns Hopkins University cohort. Results: There was a strikingly high 33% frequency of mutations within genes associated with chromatin regulation, including mutations in lysine methyltransferase 2C ( KMT2C ), lysine methyltransferase 2D ( KMT2D ), nuclear receptor binding SET domain protein 1 ( NSD1 ), CREB binding protein ( CREBBP ), E1A‐associated protein p300 ( EP300 ), and CCCTC‐binding factor ( CTCF ). In addition, the commonly altered genes phosphatidylinositol‐4, 5‐bisphosphate 3‐kinase catalytic subunit α ( PIK3CA ) and fibroblast growth factor receptor 3 ( FGFR3 ) showed distinct domain‐specific hotspot mutations in comparison with their HPV– counterparts. PIK3CA showed a uniquely high rate of mutations within the helicase domain, and FGFR3 contained a predominance of hotspot S249C alterations that were not found in HPV– HNSCC. Conclusions: This analysis represents one of the largest studies to date of HPV+ OPSCC and lends novel insight into the genetic landscape of this biologically distinct disease, including a high rate of mutations in histone‐ and chromatin‐modifying genes, which may offer novel therapeutic targets. Abstract : A high frequency of mutations within chromatin regulatory genes and domain‐specific alterations within phosphatidylinositol‐4, 5‐bisphosphate 3‐kinase catalytic subunit α ( PIK3CA ) and fibroblast growth factor receptor 3 ( FGFR3 ) are novel findings that distinguish the molecular signature of human papillomavirus–positive oropharyngeal squamous cell carcinoma from that of its smoking‐related counterpart.